Still New Chronic Q Fever Cases Diagnosed 8 Years After a Large Q Fever Outbreak. (24th May 2021) - Buijs, Sheila B; Bleeker-Rovers, Chantal P; van Roeden, Sonja E; Kampschreur, Linda M; Hoepelman, Andy I M; Wever, Peter C; Oosterheert, Jan Jelrik
Abstract: Background: Chronic Q fever usually develops within 2 years after primary infection with Coxiella burnetii . We determined the interval between acute Q fever and diagnosis of chronic infection, assessed what factors contribute to a longer interval, and evaluated the long-term follow-up. Methods: From 2007 to 2018, patients with chronic Q fever were included from 45 participating hospitals. The interval between acute and chronic infection was calculated in patients with a known day of first symptoms and/or serological confirmation of acute Q fever. Chronic Q fever-related complications and mortality were assessed by 2 investigators based on predefined criteria. Results: In total, 313 (60.3%) proven, 81 (15.6%) probable, and 125 (24.1%) possible chronic Q fever patients were identified. The date of acute Q fever was known in 200 patients: in 45 (22.5%), the interval was longer than 2 years, with the longest observed interval being 9.2 years. Patients in whom serological follow-up was performed after acute Q fever were diagnosed less often after this 2-year interval (odds ratio, 0.26; 95% confidence interval, 0.12–0.54). Chronic Q fever-related complications occurred in 216 patients (41.6%). Chronic Q fever-related mortality occurred in 83 (26.5%) of proven and 3 (3.7%) of probable chronic Q fever patients. Conclusions: Chronic Q fever is still being diagnosed and mortality keeps occurring 8 years after a large outbreak. Intervals between acute Q fever and diagnosis of chronic infection can reach more than 9 years. We urge physicians to perform microbiological testing for chronic Q fever even many years after an outbreak or acute Q fever disease. Abstract : Eight years after the largest Q fever outbreak ever reported, chronic Q fever is still being diagnosed and disease-related mortality keeps occurring. Intervals between acute Q fever and diagnosis of chronic Q fever can reach over 9 years.